2021
DOI: 10.3390/ma14206227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxide Additives on the Phase Structures and Electrical Properties of SrBi4Ti4O15 High-Temperature Piezoelectric Ceramics

Abstract: In this work, SrBi4Ti4O15 (SBT) high-temperature piezoelectric ceramics with the addition of different oxides (Gd2O3, CeO2, MnO2 and Cr2O3) were fabricated by a conventional solid-state reaction route. The effects of oxide additives on the phase structures and electrical properties of the SBT ceramics were investigated. Firstly, X-ray diffraction analysis revealed that all these oxides-modified SBT ceramics prepared presented a single SrBi4Ti4O15 phase with orthorhombic symmetry and space group of Bb21m, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Notably, recent studies have reported that Cr 2 O 3 has similarly improved the piezoelectric properties of BLSF piezoelectric materials. For instance, among modifications with MnO 2 , CeO 2 , and Cr 2 O 3 , that with Cr 2 O 3 provided the best improvement in the d 33 and thermal stability of SrBi 4 Ti 4 O 15 8 . In addition, Cr 2 O 3 addition had positive effects on the piezoelectric properties of W 6+ ‐doped Bi 4 Ti 3 O 12 and CaBi 2 Nb 2 O 9 , with an increase in the d 33 values to 28 9 and 15 pC/N 3 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, recent studies have reported that Cr 2 O 3 has similarly improved the piezoelectric properties of BLSF piezoelectric materials. For instance, among modifications with MnO 2 , CeO 2 , and Cr 2 O 3 , that with Cr 2 O 3 provided the best improvement in the d 33 and thermal stability of SrBi 4 Ti 4 O 15 8 . In addition, Cr 2 O 3 addition had positive effects on the piezoelectric properties of W 6+ ‐doped Bi 4 Ti 3 O 12 and CaBi 2 Nb 2 O 9 , with an increase in the d 33 values to 28 9 and 15 pC/N 3 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The suitable A and B -site dopants for SBT have recently shown interesting behaviors regarding the piezoelectric, ferroelectric, and pyroelectric properties. Recently, Wang et al have studied the piezoelectric and dielectric properties of SBT ceramics with the addition of different oxides, where the modified Sr 0.92 Gd 0.053 Bi 4 Ti 4 O 15 + 0.2 wt% Cr 2 O 3 has shown the best merits with piezoelectric d 33 ~ 28 pC/N [ 17 ]. Ramana et al have reported the high remnant polarization ( P r ) of ~9.2 µC/cm 2 for the A -site doping of Pb in SBT (Sr 1−x Pb x Bi 4 Ti 4 O 15 ) ceramics [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…SBT ceramic has an orthorhombic structure (space group: A2 1 am) and above the curie temperature T c =530 • C, it changes to a tetragonal structure (space group: I4/mmm) (1)(2)(3)(4) . The Bi and oxygen vacancies will be formed for SBT ceramics during the process of sintering, the oxygen vacancy maintains the neutral charge (5,6) . The oxygen vacancy may cause due to enhanced leakage current, impeding the displacement of the Ti 4+ ion, screening the electric field near the space charge region, and trapping of charge carriers (7,8) .…”
Section: Introductionmentioning
confidence: 99%
“…Some previous literature reported that substituting the A and/or B-site of SBT will improve the ferroelectric properties and minimize the oxygen vacancies (9,10) . The effect of oxide additives like Gd 2 O 3 , CeO 2 , MnO 2, and Cr 2 O 3 on the phase structures and electrical properties of SBT ceramics were investigated by Shaozhao Wang et al (11) . The oxide additives improve the piezoelectric property of SBT (d 33 = 10 pC/N); SCBT-Cr and SGBT-Cr obtained a higher d 33 of 26 pC/N and 28 pC/N, respectively.…”
Section: Introductionmentioning
confidence: 99%